SPE/IATMI Asia Pacific Oil &Amp; Gas Conference and Exhibition 2015
DOI: 10.2118/176036-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Nanosilica Concentration in Synthetic Based Mud (SBM) for High Temperature High Pressure Well

Abstract: Synthetic based mud (SBM), a non-Newtonian fluid is proven to be the optimum mud for almost all drilling operations, for example in high temperature high pressure (HTHP) well, deepwater, unconventional and long extended reach directional (ERD) well. However, at certain conditions, the good performance of SBM will degrade, particularly due to effect of chemical instability under high temperature. In the light of aforesaid concern, the study on nano particles as a smart-fluid in drilling operations has been gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…It is essential to control the formation damage during drilling to minimize operation costs or to abandon the well. In this regard, many researchers have recently conducted numerous studies to design proper drilling fluid using nanotechnology, which consists of nanomaterials to control formation damage in hydrocarbon fields. …”
Section: Application Of Nanotechnology For Formation Damage Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to control the formation damage during drilling to minimize operation costs or to abandon the well. In this regard, many researchers have recently conducted numerous studies to design proper drilling fluid using nanotechnology, which consists of nanomaterials to control formation damage in hydrocarbon fields. …”
Section: Application Of Nanotechnology For Formation Damage Controlmentioning
confidence: 99%
“…With these unique physicochemical characteristics, nanoparticles have gained wide attention and have been applied in oil and gas fields. The most used nanomaterials in the petroleum industry include silicon oxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), magnesium oxide (MgO), iron oxide (Fe 2 O 3 ), nickel oxide (NiO), and titanium dioxide (TiO 2 ) . Nano-based materials are used in drilling, ,, exploration, completion, , enhanced recovery, and stimulation techniques .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Wahid et al [5] showed that the introduction of nanosilica particles into synthetic based mud (SBM) offers a stable rheological results, thinner mud cake and 40% lesser filtrate volume up to 350.…”
Section: Overview Of Mud Cake Formationmentioning
confidence: 99%
“…Synthetic-based drilling fluids (SBDFs) are a class of high-performance oil-based drilling fluids with low environmental impact, since their continuous phase does not contain aromatics, and are composed of esters, ethers, linear alpha olefins (LAOs), isomerized olefins (IOs), or poly-alpha olefins (PAOs), which are more readily biodegradable and relatively nontoxic to most forms of life. However, chemical degradation and instability still occur when drilling through high-temperature and high-pressure formations [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%